INTEREST RATE EXPLORATION AS A STOCK RETURN PREDICTOR: INDUSTRY TYPE AND MARKET CAP APPROACH - Junaidi Junaidi; Ari Surya Dharmawan; Mohamed Omar Abdulrahim; sultan syah (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to analyze the effect of interest rates on stock returns in the banking and real estate industries. This research using a quantitative approach with associative methods to explore relationships between variables. The data used are secondary data, including interest rates, stock returns, industry type, and market capitalization, with the research population consisting of banking companies listed on the Indonesia Stock Exchange and Bank Indonesia during the period from January 1, 2016, to December 31, 2022. The sample was selected using a purposive sampling method, resulting in 16,380 observations of monthly data, with 126 respondents used in the analysis. Hypothesis testing was conducted using multiple linear regression, which revealed that interest rates have a significant negative effect on stock returns, particularly in the banking industry compared to the real estate industry. The greater sensitivity in the banking industry is attributed to differences in business characteristics and financial structures between the two industries. The novelty of this study compared to previous research lies in the object studied, the indicators used for the interest rate variable, and the examination of stock return variables moderated by industry type and market capitalization.